2022
DOI: 10.1038/s41467-022-31437-7
|View full text |Cite
|
Sign up to set email alerts
|

Structures and gating mechanisms of human bestrophin anion channels

Abstract: Bestrophin-1 (Best1) and bestrophin-2 (Best2) are two members of the bestrophin family of calcium (Ca2+)-activated chloride (Cl−) channels with critical involvement in ocular physiology and direct pathological relevance. Here, we report cryo-EM structures of wild-type human Best1 and Best2 in various states at up to 1.8 Å resolution. Ca2+-bound Best1 structures illustrate partially open conformations at the two Ca2+-dependent gates of the channels, in contrast to the fully open conformations observed in Ca2+-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 42 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…3A ). First, the functional consequences of hBEST1 345 (hBEST1 1-345 ) mutant, which encodes only transmembrane core domain ( 14 ), were accessed by the electrophysiological recordings. The hBEST1 345 showed robust [Ca 2+ ] i -dependent currents with the EC 50 of ∼470 nM (3-8 observations), which differs less than an order of magnitude (∼2.5-fold decrease) to wildtype hBEST1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…3A ). First, the functional consequences of hBEST1 345 (hBEST1 1-345 ) mutant, which encodes only transmembrane core domain ( 14 ), were accessed by the electrophysiological recordings. The hBEST1 345 showed robust [Ca 2+ ] i -dependent currents with the EC 50 of ∼470 nM (3-8 observations), which differs less than an order of magnitude (∼2.5-fold decrease) to wildtype hBEST1.…”
Section: Resultsmentioning
confidence: 99%
“…Structural studies have revealed the three-dimensional architectures of several BEST channel homologs including chicken BEST1 (cBEST1) ( 11 , 12 ), bovine BEST2 (bBEST2) ( 13 ), hBEST1, and hBEST2 ( 14 ). The structures showed that the functional BESTs are formed by the homo-pentameric assembly.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structures of future interest might include the Na + /I − symporter (NIS) (PDB: 7UV0) that mediates active I − transport and contains a highly conserved I − binding site consisting of predominantly hydrophobic and aromatic residues (15). Similarly, the Cl − -selective human bestrophin channels (hBest1& hBest2) contain a set of highly conserved hydrophobic residues within the neck of the permeation pathway (42). These structures suggest not only an important role for hydrophobic contacts in the ion permeation pathway but potentially influential roles of anion-π interactions.…”
Section: Discussionmentioning
confidence: 99%